Needed: a restorative pick-me-up - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Nutrients on the move. Soil fertility dynamics in African farming systems. Edited by T Hilhorst & F Muchuna, IIED, London. 2000. 145 pp. ISBN 1 8 99 825 568 Free to readers in ACP and other developing countries. For readers in OECD countries: GBP 12